Analytical modelling of concrete long-term and short-term strain/Betono trumpalaikių ir ilgalaikių deformacijų analitinis modeliavimas - Augonis, Mindaugas (Journal of Civil Engineering and Management, 2001)
Concrete is not a homogeneous material. However, such an approach does not enable one to precisely determine short-term or long-term strain of concrete which consists of separate materials components with different physical and mechanical properties. Therefore, concrete should be considered a composite of coarse aggregate and mortar. Such a model enables one to take into account different properties of concrete components. The creep or shrinkage of coarse aggregate can be assumed as zero. It is enough to accept only creep or shrinkage of mortar and the present model becomes simpler. In case of a long term, load stress in matrix decreases because of relaxation. Thus, part of load passes from matrix to coarse aggregate. In order to describe such a phenomenon by integro-differential equations of creep it is necessary to know stress history for each element of matrix. It would be difficult to determine creep in this way. It is by far easier to solve macromechanical model of creep by the method of effective modulus of ageing material developed by Z. P. Bazant. This method requires only the increments of stress and strain. Figs 6 and 9–12 show that present models give similar results which are quite well-coincident with present experimental data. Article in Lithuanian. First Published Online: 30 Jul 2012